To the collector belong the spoils : modernism and the art of appropriation - Pfeifer, Annie (Cornell University Press, 2023)
"Rethinks collecting as an artistic, revolutionary, and appropriative modernist practice that flourishes beyond institutions like museums or archives and examines the relationship between literary modernism and twentieth-century practices of collecting objects through three author-collectors, Walter Benjamin, Carl Einstein, and Henry James"--